2017
DOI: 10.1519/jsc.0000000000001667
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Profile and Activity Pattern of Minor Gaelic Football Players

Abstract: Cullen, BD, Roantree, M, McCarren, A, Kelly, DT, O'Connor, PL, Hughes, SM, Daly, PG, and Moyna1, NM. Physiological profile and activity pattern of minor Gaelic football players. J Strength Cond Res 31(7): 1811-1820, 2017-The purpose of this study was to evaluate the physiological profile and activity pattern in club- and county-level under-18 (U-18) Gaelic football players relative to playing position. Participants (n = 85) were analyzed during 17 official 15-a-side matches using global positioning system tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…These aggregated scores allowed for a 'readiness to train' percentage (RTT %) to be automatically calculated for each player. The subjective internal and objective external demands of collective training were quantified using RPE [30] and GPS technology respectively [1,3,4,5,6,7]. All data were categorised across the full season but also for descriptive purposes categorised into three specific phases of pre-season (Jan-Feb 2017), early in-season (Mar-June 2017), and late in-season (July-Sept 2017).…”
Section: Experimental Approach To the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…These aggregated scores allowed for a 'readiness to train' percentage (RTT %) to be automatically calculated for each player. The subjective internal and objective external demands of collective training were quantified using RPE [30] and GPS technology respectively [1,3,4,5,6,7]. All data were categorised across the full season but also for descriptive purposes categorised into three specific phases of pre-season (Jan-Feb 2017), early in-season (Mar-June 2017), and late in-season (July-Sept 2017).…”
Section: Experimental Approach To the Problemmentioning
confidence: 99%
“…Indeed, global positioning system analysis of athlete running performance has shown that these athletes cover an average distance of 8-10 km over 70 min therefore high levels of aerobic fitness are desirable [1,5,6]. However, key moments of match play such as gathering possession, evading opponents and breaking tackles demand well rounded physical qualities such as high-speed running capacity and repeated effort ability in addition to strength and power qualities [5,7]. The competition phase within elite Gaelic football runs from February-September during which teams compete for National League and All-Ireland Championship titles, playing up to 15 games between competitions [8].…”
Section: Introductionmentioning
confidence: 99%
“…The use of heart rate (HR) measurement has been suggested to be an indirect measure of exercise intensity in female team sports (44). In male U18 GF, HRpeak was observed as 81.6 6 4.3% during 60 minutes of match play (36). In addition, in adult male GF, mean HRpeak values were reported as 192 6 9 b$min 21 and average HR as 162 6 10 b$min 21 (54).…”
Section: Physiological Demandsmentioning
confidence: 99%
“…Studies carried out with the help of GPS, in team sports, highlight that the level of play does not influence the distance covered, the movement patterns of the players, or the heart rate values [16] and that specific training, individualized by the positions that they occupy, is necessary for the players on the field. Thus, analyses of the physiological profile and the training level can be generated to influence the design of position-specific training in the field [17].…”
Section: Portable Tracking Technology and Gps Global Positioning Systemsmentioning
confidence: 99%